Affirmative Inaction: Education, Language Proficiency, and Socioeconomic Attainment Among China's Uyghur Minority. Issue 4 (1st October 2016) - Tang, Wenfang; Hu, Yue; Jin, Shuai
Abstract: This study finds that the Mandarin proficiency is partially responsible for the gap in socioeconomic inequality between the Han majority and the Uyghur Muslim minority. Multiple sources of evidence show that Uyghur Muslims share equal educational attainment as the Han majority, but are noticeably less fluent in Mandarin than the Han majority. Using data from the 2012 China Labor-Force Dynamics Survey (CLDS), we find that Mandarin proficiency can significantly improve occupational attainment and income. In other words, holding other factors equal, if ethnic minorities speak better Mandarin, they would have better chances to improve their socioeconomic status.